Bi-directional block is superior to non-inducibility in predicting freedom from atrial fibrillation after pulmonary vein isolation - Sherif H. Zaky (The Egyptian Heart Journal, 2011)
Background: There is variability in the endpoints used with the different approaches to pulmonary vein (PV) isolation. Elimination of PVP recorded inside the targeted PV antrum indicates inlet block and is considered the 1st indicator of a successful PV isolation, however this may not be sufficient to predict non recurrence of AF. Aim: To compare the efficacy of two end points, pulmonary vein (PV) entrance block with non-inducibility (NI) Vs achieving PV bi-directional (BD) block in terms of freedom of AF after PV isolation (PVI) for paroxysmal/persistent atrial fibrillation (AF). Method: We included 58 consecutive patients (pts) who underwent PVI for symptomatic AF. In all pts, the end point of ablation was abolishing PV potentials (PVP) in the PVs followed by testing for bidirectional block (defined by both loss of PVP and failure to conduct to the LA by pacing at 10 mA and from 10 bipolar pairs of electrodes on a circular catheter positioned at the entrance of the PV) and/or NI of AF (by burst atrial pacing). Results: Bidirectional block was achieved in 40 patients (69%) while Non inducibility was achieved in 36 (58.5%) patients with an overlap of achieving both endpoints in 18 (31%) patients. Over a follow up period of 17 ± 11 months, 34 pts (85%) in group I Vs 22 (62%) in group II were free of AF. Correlation showed significant relation between BD block (OR = 8.07, P = 0.004) Vs NI of AF post-PVI (OR = 2.8, P = 0.095) in predicting freedom from AF at follow up. Conclusion: Achieving BD block improves results and may predict maintenance of sinus rhythm more than NI of AF after PVI. It can be used as an electrophysiological endpoint alternative to or in conjunction with non inducibility in AF ablation procedures.